Effectiveness of a structured handover tool (I-PASS + C) in patients transferred out from pediatric intensive care unit to ward: A single-center, prospective observational study from Western India - Vaibhava Upadhyay; Amit Kumar; Krutika Rahul Tandon; Somashekhar M. Nimbalkar; Saalim M. Kadiyawala (Journal of Pediatric Critical Care)
Background: Handover is a process of communication between physicians and, thus, integral to medical practice. Communication failures commonly cause preventable medical errors and adverse events. This study was done to evaluate the effectiveness of a structured handover tool. Subjects and Methods: It is a prospective observational study conducted in pediatric intensive care unit (PICU) of tertiary care hospital of Western India. The errors were noticed in the handover process of patients who were transferred from the PICU to the pediatric ward. A modified handover tool I-PASS + C was implemented as an intervention. The outcome was measured in the form of changes in the number of errors postintervention. Results: The handovers enrolled in the control group were 46 (28.04%) and 40 (24.39%) in the intervention group. Patient’s age ranged from 3 months to 205 months. “Not mentioning information regarding counseling and parent’s response/behavior” and “no cross check by hearing back from the receiver” were the most commonly noticed errors in 40 (86.9%) and 31 (67.4%) patients, respectively, which reduced significantly in the intervention group. Other commonly noticed errors during the stay in the ward were “got phone call from ward to take further information” in 16 (34.78%) patients, followed by “medical errors reported in ward” in 8 (17.4%) patients, which also reduced significantly in the intervention group. Conclusions: A structured handover tool reduces the errors of the handover process as well as adverse events, after transferring the patient from the PICU to the ward.